Enhancing Language Instruction: A Study on MTB-MLE Implementation in Urban Education - Oscar JR Ancheta; Cedric Anthony E. Ochoco (Universidade Estadual de Alagoas, 2024)
This study examines the implementation of Mother Tongue-Based Multilingual Education (MTB-MLE) within urban educational contexts. Conducted in Don Mariano Marcos Memorial State University's laboratory elementary schools, it reveals the complexities of L1 instruction. The research underscores the need for tailored teacher training, localized instructional resources, and improved support across human, material, and financial resources. Findings show that while there is considerable awareness, actual implementation and support for L1 instruction require significant improvement. These results emphasize the importance of prioritizing MTB-MLE, especially in cultivating multilingualism and enhancing the overall learning environment.